Universal health coverage, a priority or just a slogan? - Nasir Dehghan; Zeinab Ebrahimi fard (Shahid Beheshti University of Medical Sciences, 2019)
Universal Health Coverage is defined as preventive, curative and rehabilitation services which are available to all people in the community and can be accessed if needed. Improving health care coverage is directly related to the access and integration of our staff to provide integrated care for the general public. Government investment in Primary Health Care will be the cornerstone of UHC. the implementation of this approach will be challenging, and many developing countries have so far failed to achieve universal coverage due to a lack of adequate management capacity in the insurance sector, or differences in the method of calculating premiums in various organizations which have led to different effects.